Colour reading speech kit (Tubana Kit) as a therapy tool for students with special needs at Sekolah Menengah Kebangsaan Seremban 2, Seremban, Negeri Sembilan - Nazir, Faridah; Jano, Zanariah; Idrus, Azean Idruwani; Ramdzan Ali, Al Amirul Eimer; Toha @ Tohara, Abdul Jalil (UKM Press, 2024)
The Color Reading Speech Kit (Tubana Kit) is provided to improve the skills of listening, speaking, reading, observation, concentration, and interest and reduce the stress of students in special education schools. This kit consists of two items, namely activities for tongue twister training in the form of software and English and Malay activities and coloring books. This study was conducted through collaboration with the Mobile Book Café as the industry collaborator and Sekolah Menengah Kebangsaan (SMK) Seremban 2, as the community collaborator. The respondents comprised 14 special needs students, i.e. 7 students from the Malay Language class and 7 students from the English Language Class. Despite having learning disabilities, these special needs students are still able to read and write. All the students in the Malay Language and English class have profited from the Tubana Kit's knowledge transfer, according to the results obtained after utilizing it. The pupil now speaks and behaves better, with better pronunciation. Their vocabulary and articulation in both Malay and English are also on par. The use of coloring books and activities in both Malay and English has improved vocabulary usage among students who typically have low vocabulary. Indeed, SMK Seremban 2 children with special needs have demonstrated the effectiveness of the Tubana Kit as a therapy tool in both Malay and English languages.